Extracto de hojas de piñón (Jatropha curcas) como alternativa ecológica para combatir garrapatas de bovinos - Bravo Guerrero, Betty Jeritza (2023)
The purpose of this study is to evaluate the acaricidal effect of the extract of pinyon leaves (Jatropha curcas) through in vitro tests in an immersion test in Petri dishes on a population of 320 adult ticks, with a total of three treatments plus control with four repetitions, distributed as follows: T0: Amitraz at 20.8%; T1: Extract of J. curcas at 4.1%; T2: Extract at 4.24%; T3: Extract at 4.3% concentration, which were evaluated in a range of 24, 48, 72 and 96 hours, in addition, a preliminary in vivo study was carried out with the best treatment. The variables to be studied were: characterization of the extract (pH, density, refractive index, acidity and concentration of phenols), mortality and survival of ticks. For the variables with normality, a completely randomized design was used with a Tukey test at 5% probability and for the variables that do not meet the assumptions, the Kruskal-Wallys test and pairwise separation were used, where it was evidenced that T2 ( 20.00 ± 0.00) stood out significantly among the treatments, demonstrating greater in vitro acaricidal effectiveness at 96 hours evaluated, while T0 (1.75 ± 0.50) and T1 (2.25 ± 0.50 ) obtained the highest survival values, the in vivo study applied with T2 showed that the highest tick mortality was obtained at 96 hours (249,67 ±112,96), validating the potential use of the extract of pine nut leaves as an ecological alternative to combat bovine ticks.